Pengembangan Perangkat Pembelajaran Biologi Berbasis Kearifan Lokal Kerinci pada Materi Keanekaragaman Hayati untuk Siswa MAS: The Development of Biology Learning Toolswith Kerinci’s Local Wisdom-Based on Biodiversity Material for Senior High Schools - Dodo Tomi; Evita Anggereini; Muhaimin Muhaimin (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2018)
Integrating local wisdom with the concept of biodiversity is a learning innovation that can build cultural character for students to conserve the surrounding environment, including in maintaining cultural and social values. This study aims to develop local wisdom-based learning tools on biodiversity material. This research and the development employed the model used is a 4-D model, which consists of define, design, development and disseminate. Learning tools that are developed based on local wisdom can increase students’ interest in the science learning process. The response of the Koto Rendah Private Islamic High School biology teachers to the lesson plans is in the "Good" category. The developed students’ worksheet also obtained the similar response which is in the "Good" category. The results of small group trials obtained an average score of 31.67 with a percentage of 79.17% (good category). The large group trial results obtained an average score of 31.45 with a percentage of 78.63% (good category). The developed local wisdom-based learning instrument can be categorized as good to be used in learning in the Koto Rendah Private Islamic High School.